Valence-band density of states and surface electron accumulation in epitaxial SnO2 films - WATSON, GRAEME (My University, 2014)
The surface band bending and electronic properties of SnO 2 (101) films grown on r -sapphire by plasma-assisted molecular beam epitaxy have been studied by Fourier-transform infrared spectroscopy (FTIR), x-ray photoemission spectroscopy (XPS), Hall effect, and electrochemical capacitance-voltage measurements. The XPS results were correlated with density functional theory calculation of the partial density of states in the valence-band and semicore levels. Good agreement was found between theory and experiment with a small offset of the Sn 4 d levels. Homogeneous Sb-doped SnO 2 films allowed for the calculation of the bulk Fermi level with respect to the conduction-band minimum within the k · p carrier statistics model. The band bending and carrier concentration as a function of depth were obtained from the capacitance-voltage characteristics and model space charge calculations of the Mott-Schottky plots at the surface of Sb-doped SnO 2 films. It was quantitatively demonstrated that SnO 2 films have downward band bending and surface electron accumulation. The surface band bending, unoccupied donor surface-state density, and width of the accumulation region all decrease with increasing Sb concentration.
PUBLISHED
Keywords: plasma-assisted molecular beam; plasma-assisted molecular beam